A novel technique using ultrasonography in upper airway management after anterior cervical decompression and fusion - Shizumasa Murata; Hiroshi Iwasaki; Hiroyuki Oka; Hiroshi Hashizume; Yasutsugu Yukawa; Akihito Minamide; Shunji Tsutsui; Masanari Takami; Keiji Nagata; Ryo Taiji; Takuhei Kozaki; Hiroshi Yamada (BMC Medical Imaging, 2022)
Abstract Background Airway complications are the most serious complications after anterior cervical decompression and fusion (ACDF) and can have devastating consequences if their detection and intervention are delayed. Plain radiography is useful for predicting the risk of dyspnea by permitting the comparison of the prevertebral soft tissue (PST) thickness before and after surgery. However, it entails frequent radiation exposure and is inconvenient. Therefore, we aimed to overcome these problems by using ultrasonography to evaluate the PST and upper airway after ACDF and investigate the compatibility between X-ray and ultrasonography for PST evaluation. Methods We included 11 radiculopathy/myelopathy patients who underwent ACDF involving C5/6, C6/7, or both segments. The condition of the PST and upper airway was evaluated over 14 days. The Bland–Altman method was used to evaluate the degree of agreement between the PST values obtained using radiography versus ultrasonography. The Pearson correlation coefficient was used to determine the relationship between the PST measurement methods. Single-level and double-level ACDF were performed in 8 and 3 cases, respectively. Results PST and upper airway thickness peaked on postoperative day 3, with no airway complications. The Bland–Altman bias was within the prespecified clinically nonsignificant range: 0.13 ± 0.36 mm (95% confidence interval 0.04–0.22 mm). Ultrasonography effectively captured post-ACDF changes in the PST and upper airway thickness and detected airway edema. Conclusions Ultrasonography can help in the continuous assessment of the PST and the upper airway as it is simple and has no risk of radiation exposure risk. Therefore, ultrasonography is more clinically useful to evaluate the PST than radiography from the viewpoint of invasiveness and convenience.